Differentiation of Memory CD8 T Cells Unravel Gene Expression Pattern Common to Effector and Memory Precursors - Neitzke-Montinelli, Vanessa; Calôba, Carolina; Melo, Guilherme; Frade, Bianca B.; Caramez, Enzo; Mazzoccoli, Luciano; Gonçalves, André N. A.; Nakaya, Helder I.; Pereira, Renata M.; Werneck, Miriam B. F.; Viola, João P. B. (Frontiers in Immunology, 2022)
Long-term immunological protection relies on the differentiation and maintenance of memory lymphocytes. Since the knowledge of memory generation has been centered on in vivo models of infection, there are obstacles to deep molecular analysis of differentiating subsets. Here we defined a novel in vitro CD8 T cell activation and culture regimen using low TCR engagement and cytokines to generate differentiated cells consistent with central memory-like cells, as shown by surface phenotype, gene expression profile and lack of cytotoxic function after challenge. Our results showed an effector signature expressed by in vitro memory precursors and their plasticity under specific conditions. Moreover, memory CD8 T cells conferred long-term protection against bacterial infection and slowed in vivo tumor growth more efficiently than effector cells. This model may allow further understanding of CD8 T cell memory molecular differentiation subsets and be suited for generating cells to be used for immunotherapy.